The Influencing Effect Of Slogans In Segment Of Children - Robert Sandor Szucs (European Scientific Journal, ESJ, 2016)
Nowadays children face lots of slogans every single day. A good slogan generates feelings. Of course these feelings, brand names and slogans can be placed in mind of children by marketing experts. The remember rate of slogans is shockingly high, higher than is case of their parents. We can state that well-placed slogans play a very important role in influencing of children. All of these contribute to the development of brand loyalty, which – if it develops during childhood – can last an entire lifetime. My primary research (sample size is 1222 children) shows the remember rate of slogans and brand names in case of different foods with high level of fat-, sugarand/or salt content.